2016
DOI: 10.3109/0886022x.2015.1136895
|View full text |Cite
|
Sign up to set email alerts
|

Flax lignan concentrate reverses alterations in blood pressure, left ventricular functions, lipid profile and antioxidant status in DOCA-salt induced renal hypertension in rats

Abstract: Context Earlier we reported cardioprotective, antihyperlipidemic, and in vitro antioxidant activity of flax lignan concentrate (FLC) obtained from the seeds of Linum usitatissimum L. (Linaceae). Objective To investigate the effect of FLC in deoxycorticosterone acetate (DOCA)-salt induced experimental renal hypertension in rats. Materials and methods Hypertension was induced in uninephrectomized (UNTZD) male Wistar rats (230-280 g) by injecting DOCA (25 mg/kg, subcutaneously, twice weekly) and supplementing 1% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 79 publications
2
7
0
Order By: Relevance
“…These results confirm those reported by Ghule et al (2012) who showed that an ethanolic extract of flaxseed attenuates the rise in blood pressure. The similar results were found also by Sawant and Bodhankar(2016), in lignane extract (FLC)-treated hypertensive rats obtained from L. usitatissimum L. (Linaceae) seeds. In fact, the antihypertensive effect obtained is attributed to its opulence in lignan composition such as SDG.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These results confirm those reported by Ghule et al (2012) who showed that an ethanolic extract of flaxseed attenuates the rise in blood pressure. The similar results were found also by Sawant and Bodhankar(2016), in lignane extract (FLC)-treated hypertensive rats obtained from L. usitatissimum L. (Linaceae) seeds. In fact, the antihypertensive effect obtained is attributed to its opulence in lignan composition such as SDG.…”
Section: Discussionsupporting
confidence: 83%
“…Presently, flaxseed has been drawing increasing scientific attention for its potential role in preventing cardiovascular diseases (CVD) (Tirgar and Kalpesh, 2017). However, the flaxseeds possess anti-hypertensive (Ghule et al , 2012; Sawant and Bodhankar, 2016) and antihyperlipidemic properties (Dali et al , 2019; Zanwar et al , 2014), that might be beneficial to prevent the atherosclerotic plaques (Francis et al , 2013). Additionally, they also possess anti-oxidant (Cameron et al , 2013) and anti-inflammatory activities (Kaithwas and Majumdar, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Both linseed oil and SDG prevented the increase in systolic blood pressure in rats with metabolic syndrome induced by feeding with 30% fructose, likely due to decreased oxidative stress [34]. In deoxycorticosterone acetate (DOCA)-salt hypertensive rats, linseed lignan concentrate lowered blood pressure, and improved antioxidant status, serum electrolytes, and lipid profiles [35]. A lignan-enriched linseed powder reduced blood pressure, body weight, and fat accumulation, and improved lipid profiles in rats fed a high-fat and high-fructose diet [36].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, in animal studies, flaxseed protein hydrolysates and flax oil decreased blood pressure in the spontaneously hypertensive rat in acute or chronic conditions, respectively [26,27]. As well, a flaxseed lignan concentrate reduced blood pressure in the deoxycorticosterone acetate (DOCA-salt) induced renal hypertensive rats [28] and in the high fat, high sugar-fed rat [29].…”
Section: Dietary Flaxseed and Cardiovascular Diseasementioning
confidence: 99%